Analisis Perlindungan Anak Terhadap Pornografi di dalam Game Online - Idran, Mohammad; Hidayah, Indri Melawati (Legalita, 2024)
The rapid development of gaming in major Indonesian cities is evident through the proliferation of online games offering extensive multiplayer features, both locally (LAN) and online. However, many of these games contain negative elements such as violence, harassment, and even pornography, posing significant concerns for child protection. Addressing this issue, this research aims to examine the lack of clear legal safeguards for children against pornography in online gaming. The study poses two main questions: (1) How is the protection of children against pornography in online games currently implemented? (2) What are the factors impeding such protection? Through an empirical approach, combining field studies and literature reviews, data collection and processing procedures such as identification, editing, coding, and drawing conclusions are employed. The findings highlight the absence of robust legal enforcement mechanisms safeguarding children from online gaming-related pornography. Despite the imperative nature of such protection in our increasingly technologically advanced society, clear legal frameworks are lacking. This research underscores the urgency for policymakers and stakeholders to address this gap and implement effective measures to ensure the safety and well-being of children engaging in online gaming activities.